PENYULUHAN TENTANG STRATEGI PENINGKATAN STATUS DESA BERKEMBANG MENJADI MAJU DAN MANDIRI - Tajuddin, Tajuddin; Syarif, Muhammad; Natsir, Muhammad; Ariani, Wa Ode Rachmasari; Surianti, Surianti (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Rural development in Indonesia aims to address the development gap between urban and rural areas. Village development is expected to improve rural welfare and independence. Efforts to realize equitable development and welfare are carried out through various innovations such as the Village Fund Programm and Village Smart. This goal is pursued through programs such as the Village Fund, Smart Village, and Village Development Index (IDM). This counselling aims to increase the understanding of village officials regarding strategies to improve the status of villages to develop into developed and independent villages. The methods used are presentation, discussion, and evaluation through pre-test and post-test. The results of the activity showed an increase in participants' understanding of the concept of IDM. This counselling successfully provided participants with insights into data-driven development planning using IDM, although further exploration of several technical aspects is still needed.